2021
DOI: 10.1016/j.jag.2021.102301
|View full text |Cite
|
Sign up to set email alerts
|

Lockdown effects on total suspended solids concentrations in the Lower Min River (China) during COVID-19 using time-series remote sensing images

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 27 publications
1
24
0
4
Order By: Relevance
“…The absolute time differences between the sampling dates and the satellite images were within five days, with 77.14% within two days (Figure 2). In remote-sensing applications, this time difference is acceptable [59][60][61]. MODIS data (MOD09GA: reflectance production data with a spatial resolution of 500 m) were downloaded from https://ladsweb.modaps.eosdis.nasa.gov/ (accessed on 2 July 2021), while Sentinel 2 and Landsat data were acquired from the US Geological Survey website at http://lglovis.usgs.goc/ (accessed on 2 July 2021).…”
Section: Data Source and Pre-processingmentioning
confidence: 99%
“…The absolute time differences between the sampling dates and the satellite images were within five days, with 77.14% within two days (Figure 2). In remote-sensing applications, this time difference is acceptable [59][60][61]. MODIS data (MOD09GA: reflectance production data with a spatial resolution of 500 m) were downloaded from https://ladsweb.modaps.eosdis.nasa.gov/ (accessed on 2 July 2021), while Sentinel 2 and Landsat data were acquired from the US Geological Survey website at http://lglovis.usgs.goc/ (accessed on 2 July 2021).…”
Section: Data Source and Pre-processingmentioning
confidence: 99%
“…It was found that the mean turbidity showed a 24.9% decline from 33.4 NTU to 25.1 NTU after the lockdown in Wuhan, which dropped 16.0% compared to that in the previous year (Sun et al 2021). Later, when investigating the lockdown effects of the COVID-19 on total suspended solids (TSS) concentrations in the Lower Min River (China) during COVID-19 using different multi-temporal optical remotely sensed images acquired from November 2019 to April 2020 such as Landsat-5 Thematic Mapper (TM), Landsat-8 Operational Land Imager (OLI), and China's GaoFen-1 (GF-1) Wide Field of View (WFV) images, Xu et al (2021) indicated that the lockdown measures have resulted in a 48% fall in TSS concentrations in February 2020. Xu et al (2021) also concluded that industrial production, social and economic activities, and river shipping appear to be the main factors contributing to the river's TSS decline in the lockdown period.…”
Section: Studies Of Impacts On Water Qualitymentioning
confidence: 99%
“…Numerous studies have assessed spatio-temporal changes of natural environments during this epidemic, such as the improved air quality and water quality ( Venter et al, 2020 , Xu et al, 2021 ). However, the impact of the lockdown of cities on our socioeconomic systems is more complicated and hidden ( Beyer et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%